Effect of Competence-Based Human Resource Management on The Performance of Millennial Employees in The ISP Batam Indonesia and Personal Value as Intervening Variable - Nolla Puspita Dewi; Bambang Satriawan; Nurhatisyah Nurhatisyah (International Forum of Researchers and Lecturers, 2025)
Research aims: This study aims to examine the impact of Competency-Based Human Resource Management (CBHRM) on the performance of millennial employees in the Internet Service Provider (ISP) sector in Batam, Indonesia. Additionally, the research investigates the role of personal values as a moderating variable in the relationship between CBHRM and employee performance. Design/Methodology/Approach: A quantitative research method was used, collecting data from 86 millennial employees through structured questionnaires. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). Research findings: CBHRM significantly improves millennial employee performance and influences personal values. However, personal values do not directly affect performance but strengthen the impact of CBHRM. This highlights the importance of integrating CBHRM with value-based HR policies to optimize workforce productivity. Theoretical Contribution/Originality: This study provides empirical evidence of CBHRM’s effectiveness and expands knowledge on how personal values interact with HRM practices to enhance employee performance. Practitioners/Policy Implications: Organizations should integrate CBHRM with value-driven leadership and training programs to maximize employee engagement. Policymakers should promote CBHRM adoption to address workforce skill gaps in technology-driven industries. Research Limitations/Implications: This study is limited to a single ISP company in Indonesia, which may restrict the generalizability of the findings. Future research should expand the sample size and explore other industries to validate the results. Additionally, further studies should investigate the influence of other moderating variables such as leadership style and organizational culture on the CBHRM-performance relationship